Effect of Sustainability Reporting Disclosure on Financial Performance With NPL as Moderator (2020-2024) - Fuadi, Irwan; Yusrianti, Hasni; Ferina, Ika Sasti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the effect of sustainability reporting disclosure on financial performance among finance companies in the Indonesian banking sector from 2020 to 2024, with Non-Performing Loans (NPL) as a moderating variable. Using Stakeholder Theory, Legitimacy Theory, and Signaling Theory as the conceptual foundation, the research analyzes sustainability disclosure based on POJK No. 51/POJK.03/2017 and SEOJK No. 16/SEOJK.04/2021. A quantitative descriptive approach was applied using secondary data obtained from sustainability reports and financial statements of companies listed on the Indonesia Stock Exchange. The sample consists of 20 firms selected through purposive sampling from a population of 106 companies. Panel data regression with EViews was used, supported by classical assumption tests and model selection techniques including the Chow, Hausman, and Lagrange Multiplier tests. The findings reveal that economic aspect disclosure significantly improves financial performance (ROE), driven by enhanced investor trust and transparency in financial management. However, environmental and social disclosures do not significantly affect ROE. NPL moderates the relationship between economic and environmental disclosures and financial performance, where higher NPL weakens the impact of economic disclosure, while lower NPL enhances the effectiveness of environmental disclosure. NPL does not moderate the social disclosure ROE relationship. Overall, sustainability reporting and NPL jointly influence financial performance through improved transparency and risk management.